2020
DOI: 10.1590/1984-0462/2020/38/2018363
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Meals Consumed by Brazilian Adolescents and Associated Habits: Systematic Review

Abstract: ABSTRACT Objective: To analyze the studies that identified the frequency of meals ingested by Brazilian adolescents and associated habits. Data sources: A systematic search was made in the databases and electronic databases: MEDLINE/PubMed, The Latin American and Caribbean Center of Information in Health Sciences (BIREME), Scopus, Web of Science and Embase, with articles published between January/2007 until December/2017, which addressed the evaluation of the frequency of meals performed by adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The omission of breakfast and the substitution of meals for quick snacks is a common habit among adolescents. 25 The study indicated a positive association between skipping breakfast and markers of global and abdominal adiposity (BMI, waist circumference, waist-to-height ratio) regardless of sex. Breakfast should provide 25% of the recommended daily energy intake, and the omission habit contributes to an unbalanced diet and increased energy intake throughout the day.…”
Section: Discussionmentioning
confidence: 87%
“…The omission of breakfast and the substitution of meals for quick snacks is a common habit among adolescents. 25 The study indicated a positive association between skipping breakfast and markers of global and abdominal adiposity (BMI, waist circumference, waist-to-height ratio) regardless of sex. Breakfast should provide 25% of the recommended daily energy intake, and the omission habit contributes to an unbalanced diet and increased energy intake throughout the day.…”
Section: Discussionmentioning
confidence: 87%
“…Added to this is the fact that individuals with lower purchasing power may not have access to fresh fruits and vegetables at affordable prices, in addition to not having the nutritional knowledge, skills, or control of resources to buy and prepare necessary foods for a healthy diet (WHO, 2018). It is recognized that high consumption of ultra-processed foods may contribute to negative outcomes such as increased chance of developing obesity, diabetes, dyslipidemia, and other nutritional problems in adolescents (Barufaldi et al, 2016;Ruiz, Zuelch, Dimitratos & Scherr, 2019;Malik, Pan, Willett & Hu, 2013 The meal consumption pattern, as in other studies (Sousa, 2020), revealed a high prevalence of irregular breakfast among adolescents, which is a major concern for health professionals. Individuals who habitually eat breakfast are more likely to ingest nutrients in the proper amount, have better cognitive academic performance, and have a lower chance of developing excess body weight (Barufaldi et al, 2016;Barr, Vatanparast & Smith, 2018;Gaal, 2018& Adolphus, Lawton, Champ, & Dye, 2016 , which is why the regular practice of this meal should always be encouraged among young people.…”
Section: Discussionmentioning
confidence: 88%
“…Sugary drinks are associated to weight gain and increased risk of obesity (Alcalá and Sharif, 2017; Barac et al, 2015; Barbosa et al, 2021; Barnett, 2018; Barro et al, 2020; Bleich and Wolfson, 2015; British Soft Drinks Association Annual Report, 2016; Bruce et al, 2018; Carran et al, 2016; Chan et al, 2020; Cheikh Ismail et al, 2020; Das, 2016; den Biggelaar et al, 2020; Donazar-Ezcurra et al, 2018; Evers et al, 2018; Feig et al, 2008; Fenwick et al, 2018; Ferreira-Pêgo et al, 2016; Ganss, 2006; Gardener et al, 2018; Goodman et al, 2016; Gravelle et al, 2015; Guo et al, 2014; Hallfrisch, 1990; Harrell et al, 2015; Hrolfsdottir et al, 2019; Hu et al, 2018; Husárová et al, 2017; Imamura et al, 2016; Jameel et al, 2016; Johnson et al, 2010; Ju et al, 2019; Kadel et al, 2020; Kashino et al, 2021; Koekkoek et al, 2017; Kwak et al, 2019; Lin et al, 2016; Lin et al, 2021; Malik and Hu, 2015; Malik and Hu, 2022; Pauli and Repke, 2017; Sousa et al, 2020). They can promote weight gain through adverse effects on metabolism, due to their ability to induce rapid spikes in blood glucose and insulin levels (Solomi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results from a study that evaluated the frequency of food consumption during COVID-19 showed that soft drinks were the only unhealthy eating marker more frequently consumed by non-isolated families (Teixeira et al, 2021). This may be explained by the fact that these families live in more economically developed regions and substitute large meals for snacks (Sousa et al, 2020). Habitual consumption of foods and drinks rich in sweets, soft drinks, and sugar-sweetened beverages are associated with an increased risk of dental caries, excess body weight, diabetes, and cardiovascular diseases (Teixeira et al, 2021).…”
Section: Challenge and Necessity Of Dietary Management In Soft Drink ...mentioning
confidence: 99%